Mempertahankan Rumah Lanting sebagai Warisan Budaya Sungai: Tindakan Sosial Penghuni dan Peran Pemerintah Kota Banjarmasin - Yuli Apriati; Cucu Widaty; Salamat Riyani; Meysha shifa Azzahra; Alya Fatima Azzahra; Putri Septiana; Shelvanesa Febrianti (PADARINGAN (Jurnal Pendidikan Sosiologi Antropologi), 2026)
Floating houses are one of the river cultural heritages of the Banjar community that represent the identity of riverside settlements in Banjarmasin. However, urban modernization, shifts in community orientation, and weak preservation regulations have contributed to the continuous decline in the existence of floating houses. This condition indicates a threat to the sustainability of river culture, which has long been a distinctive characteristic of Banjarmasin City. This study aims to analyze the social actions of residents in maintaining floating houses and to examine the role of the Banjarmasin City government in preservation efforts in Seberang Mesjid Village. This study employed a qualitative approach using purposive sampling techniques. Data were collected through observation, in-depth interviews, and documentation involving floating house residents and local government officials associated with riverside area management. Data analysis was conducted through data reduction, data display, and conclusion drawing using Max Weber’s social action perspective as the analytical framework. The findings reveal that the residents’ social actions in preserving floating houses are carried out through routine maintenance practices, foundation repairs, the use of alternative materials, and the preservation of local values and traditions passed down across generations. Meanwhile, the government acts as a facilitator and innovator through riverside beautification programs, CSR-based assistance for floating house renovations, and the formulation of sustainable floating house development strategies. This study concludes that the sustainability of floating houses depends not only on the adaptive capacity of riverine communities but also on more integrated government policies aimed at preserving river culture in Banjarmasin City.